The economic impact of political instability: micro and macro estimates, with applications to the Arab Spring - Matta, Samer (2017)
This thesis examines the economic effects of mass political instability events, first of the Arab Spring on Tunisia from a macro and micro perspective, and then more broadly, how economies recover from such events. In addition to an introduction and conclusion, this thesis is composed of three self-contained empirical studies, which we term as chapters hereinafter. Chapter 2 uses the Synthetic Control Methodology to estimate the output loss in Tunisia as a result of the “Arab Spring”. Our results suggest that the loss was 5.5 percent, 5.1 percent, and 6.4 percent of GDP per capita in 2011, 2012, and 2013, respectively. These findings are robust to a series of tests, including placebo tests, and are consistent with those from an Autoregressive Distributed Lag model. Moreover, we find that investment was the main channel through which the economy was adversely impacted by the Arab Spring. Chapter 3 extends the analysis to a micro level and explores the impact of political instability that stemmed from the Arab Spring on Tunisian firms. Using a new dataset, we show that political instability was a major concern for small and exporting firms as well as for those that were operating in the tourism sector, those that have suffered from vandalism and those that were located in the interior region of Tunisia. Most importantly, we find that political instability was the most damaging constraint to firm growth after the Arab Spring.